2016
DOI: 10.1194/jlr.m062794
|View full text |Cite
|
Sign up to set email alerts
|

A novel diacylglycerol kinase α-selective inhibitor, CU-3, induces cancer cell apoptosis and enhances immune response

Abstract: Diacylglycerol kinase (DGK) phosphorylates diacylglycerol (DG) to generate phosphatidic acid ( 1-6 ). To date, 10 mammalian DGK isozymes ( ␣ , ␤ , ␥ , ␦ , , , , , , and ) have been identifi ed. These DGK isozymes are divided into fi ve groups (type I-V) according to their structural features ( 1-6 ). Type I DGK isozymes (DGKs ␣ , ␤ , and ␥ ) commonly contain tandem repeats of two EFhand motif domains and are classifi ed as members of the EF-hand family of Ca 2+ binding proteins. In addition to the Ca 2+ bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 67 publications
11
104
0
Order By: Relevance
“…Probably the most robust method for detecting such changes is by using mass spectrometry. However, this has proven to be difficult without genetic manipulations [8,12,43]. Using LC-MS, we analyzed changes in DAG, PA and PC in cells expressing endogenous DGKs after treatment with ritanserin and R59022 but could not obtain statistically significant results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably the most robust method for detecting such changes is by using mass spectrometry. However, this has proven to be difficult without genetic manipulations [8,12,43]. Using LC-MS, we analyzed changes in DAG, PA and PC in cells expressing endogenous DGKs after treatment with ritanserin and R59022 but could not obtain statistically significant results.…”
Section: Resultsmentioning
confidence: 99%
“…Currently available chemical tools for understanding the role of DGKs in biology and disease are confined to the two long-known inhibitors, R59022 and R59949 (DGK inhibitor I and II, respectively) [10,11]. Very recently, another small molecule, CU-3, was identified as a novel DGKα inhibitor in vitro [12]. The selectivity of R59022 and R59949 for the different DGK isotypes has been debated.…”
Section: Introductionmentioning
confidence: 99%
“…A,B). 18:1/18:1‐ and 16:0/18:1‐PA are relatively abundant species in mammalian (mouse) brain and COS‐7 cells . We recently demonstrated that DGKδ produced 14:0/16:0‐, 14:0/16:1‐, 16:0/16:0‐, 16:0/16:1‐, 16:0/18:0‐, and 16:0/18:1‐PA in glucose‐stimulated C2C12 cells .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, current DGK inhibitors consist of compounds with poor specificity within the DGK superfamily (de Chaffoy de Courcelles et al, 1989; de Chaffoy de Courcelles et al, 1985) or lack selectivity measurements against other lipid and protein kinases (Boroda et al, 2017; Liu et al, 2016; Purow, 2015). Thus, methods that provide information on small molecule binding mode and selectivity are needed to guide development of isoform-selective DGK inhibitors.…”
Section: Introductionmentioning
confidence: 99%